Person, process and practice of mentoring a module program for speech-language pathologists. - Sadicon, Maria Eusebia Catherine S.
The practice of speech-language pathology (SLP) calls for extensive and intensive work in the delivery of quality service to the disability population. Issues such as complexity of cases being handled, lack of professional preparedness and limited competence are common in the SLP profession. Corollary to this, mentoring has been repeatedly cited as an answer to these concerns. There is a dearth, through, in data-driven local studies on SLP mentoring. This study then identified the needs in the SLP field and explored the different components of SLP mentoring. Mentor and mentee characteristics, process of mentoring were determine. A mentoring guide was also crafted as an output of the study. Twenty-two Filipino speech-language pathologists and three international experts participated in focus group discussions, narrative inquiry and expert consultation. Analysis of the data showed patience, authenticity and respect as the primary characteristics of an SLP mentor. Being committed and having a sense of initiative were pegged for the SLP mentee. The study also generated specific parts in the mentoring process such as setting of goals and expectations, evaluations of outcomes and closure. Practices, on the other hand, included the more specific strategies like observations, modeling, counseling and reflection. Thematic analysis brought forth certain themes. Mentoring as a spontaneous practice and a relationship to be cultivated emerged. Lastly, the transformative facet of mentoring was exemplified by the metamorphosis of mentees and the altruistic actions of the mentors.